Incumbents' Behavior and Strategic Interactions Among Local Governments: The Case of Indonesia - Akhmad Syakir Kurnia; Syahid Izzulhaq; Sandy J. Maulana (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This paper investigates Yardstick Competition among local governments in decentralized Indonesia by distinguishing bad from good incumbent behavior. By doing so, this paper provides a more explicit connection between theoretical foundation and empirical investigation, where political incumbency is viewed based on the political economy perspective. Given that voters can compare and benchmark their incumbent's performance, an incumbent who aims for the throne twice must consider neighboring local governments' performance as the reference, leading to strategic interaction across local governments. We conduct empirical examinations using Two-regime Spatial Econometrics for panel data consisting of 99 local governments in the West, Central, and East Java Provinces from 2010 to 2017. Our empirical estimation results confirm that mimicking behavior by bad incumbents, characterized by the underperformed public sector, is evident. Bad incumbents mimic their neighbor's public spending. However, we find no evidence of Yardstick Competition by incumbents in general.